Simulation of decompressive craniectomy for ischaemic stroke treatment: A computational study - Aina Najwa, Nadzri; Mohd Jamil Mohamed, Mokhtarudin; Wan Naimah, Wan Ab Naim; Payne, Stephen J. (2021)
To evaluate the effectiveness of DC in treating brain tissue swelling using computational study based on capillary filtration and poroelastic theory.